Preparation method and application of graphene integrated middle layer for ceramic-based composite material brazing
The integrated intermediate layer of graphene three-dimensional structure was prepared through laser direct writing technology, which solved the problems of poor temperature resistance, difficult interface structure and high thermal stress in brazing of ceramic matrix composite materials and high-temperature alloys, and achieved high strength and resistance High temperature and low stress connection effect.
Patent Information
- Application Number
- CN202411634011.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
In the brazing of ceramic matrix composite materials and high-temperature alloys, there are problems such as poor temperature resistance, difficult interface structure to regulate, and large thermal stress of the joint, making it difficult to achieve high-temperature, high-quality and low-stress connections.
The three-dimensional graphene structure is prepared by laser direct writing technology, forming an integrated intermediate layer and the brazing material composite. Through ultra-short pulse laser, the composite of the three-dimensional porous graphene layer and the substrate material is prepared. to transform the intermediate layer.
The high-strength connection between ceramic matrix composite materials and high-temperature alloys is realized, the temperature resistance of the joint is improved, the interface structure is regulated, the residual stress is relieved, and the joint is resistant to high temperature, high strength and low stress is obtained.
Smart Images

Figure CN119462194A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of micro-nano connection and brazing, and more specifically to a method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials and its application. Background Art
[0002] With the rapid development of my country's aerospace and other national defense industries, the requirements for product manufacturing technology have also increased. As the "crown jewel of industry", aircraft engines have attracted much attention in recent years, and their thrust-to-weight ratio is the core indicator of engine iteration and update. The main way to improve the thrust-to-weight ratio is to achieve high temperature resistance and lightweight of hot end components such as turbine guide vanes, combustion chamber flame tubes, and tail nozzle seals. As a key material for hot end components, high-temperature resistant ceramic-based composites require more complete technical upgrades and stricter application standards. Ceramic-based composites are limited in their application in large-scale complex components due to their own hardness and brittleness. Brazing is the main technology for preparing large-scale, high-reliability, and high-quality connection structural parts of high-temperature resistant ceramic-based composites and high-temperature alloys. The bonding area between ceramic-based composites and high-temperature alloys is usually the weakest position in the entire component. At present, there are still problems that need to be solved, such as poor temperature resistance of joints, difficult to control interface structure, and large thermal stress of joints.
[0003] Laser direct writing is a new method for laser micro-nano manufacturing. It is mainly aimed at the manufacturing needs of three-dimensional complex curved micro-nano structures of difficult-to-process materials in the fields of aerospace, national defense, etc. It can achieve precise control of device performance and solve the technical difficulties of efficient, high-precision and low-cost manufacturing of large-area nanostructures. Combining it with brazing technology is expected to achieve high-quality connections from nano to macro.
[0004] Graphene has excellent performance in light-electricity-force-heat and other properties as a reinforcement material. Graphene is a single-layer or multi-layer honeycomb material in which carbon atoms are connected by covalent bonds. In the field of brazing, graphene is often used as a reinforcing phase of alloy brazing materials to prepare graphene-enhanced composite brazing materials, which have extremely low linear expansion coefficients and high temperature resistance, can balance the huge differences between heterogeneous parent materials and improve the temperature resistance of brazed joints. At present, metal three-dimensional foams or graphene metal foams are often added to the heterogeneous brazing of ceramic-based composite materials with high-temperature alloys. Although residual stress can be relieved, the metal skeleton has poor temperature resistance and cannot meet high temperature requirements. Patents such as CN113231706A and CN104625283A disclose three-dimensional structures using metal skeletons. These methods cannot achieve the long-term action mechanism of stress relief and will melt and fail in the subsequent brazing process. At the same time, the three-dimensional structure used cannot be customized so that it cannot accurately have an applicable cell shape, thickness and porosity. Previous studies mainly assembled the parent material, the brazing material, and the intermediate layer and then brazed them. This method is simple and convenient, but it is inevitable that the material will shift when moved into the furnace, resulting in poor brazing effect. CN109292759 A discloses a method for preparing graphene by laser direct writing, but its structure is limited to a two-dimensional mode, and this method cannot be applied to the brazing of high-temperature resistant ceramic-based composite materials.
[0005] Therefore, the use of laser direct writing technology to prepare graphene three-dimensional structures can precisely customize graphene layers with multiple forms and properties; the graphene layer and the brazing material are integrated through ultrashort pulse lasers. This controllable integrated brazing intermediate layer will effectively regulate the interface structure, release residual stress, and improve temperature resistance, solving the current technical problems and development bottlenecks of the hot end components of aviation engines. Summary of the invention
[0006] The purpose of the present invention is to solve the problem of high-temperature, high-quality and low-stress connection of hot-end components of aircraft engines. Graphene with a three-dimensional structure is prepared by laser direct writing, and an integrated intermediate layer can be obtained. It is applied to the brazing of ceramic-based composites, which can realize high-strength connection components of heterogeneous materials from nano to macro scale of ceramic-based composites. The inherent problems of brazing of ceramic-based composites are solved through the specialization and customization of the preparation of the graphene integrated intermediate layer.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials comprises the following steps:
[0009] (1) Selecting a brazing filler metal suitable for ceramic matrix composites as the base material;
[0010] (2) coating the organic carbon source: spin-coating the solid organic carbon source uniformly onto the surface of the substrate material according to the size of the solder to prepare an organic carbon source coating of uniform thickness;
[0011] (3) Laser direct writing to prepare three-dimensional graphene structure: Under the protection of inert gas, ultrashort pulse laser is used to directly write and ablate the surface of the organic carbon source coating according to the set path and focus depth, so that the three-dimensional porous graphene layer prepared by direct writing and the substrate material form a composite integrated intermediate layer;
[0012] (4) Clean the excess graphene layer and cover the graphene layer with another piece of brazing material of the same size and composition to form an integrated three-dimensional structure of the graphene composite brazing material, which is then assembled with the base material to be welded to form a ceramic-based composite material brazing sample and connected by vacuum brazing.
[0013] Preferably, the method for preparing the base material in step (1) comprises: if the solder is a powder, pressing the solder into sheets to obtain a sheet solder having a thickness of ≤0.2 mm as the base material;
[0014] If the solder is in sheet form, select a sheet solder with a thickness of ≤0.2 mm as the base material;
[0015] The size of the sheet solder should be at least 0.1 mm larger than the size of the surface to be soldered.
[0016] The beneficial effects brought about by the above optimization include: the sheet structure can easily achieve uniform distribution of the three-dimensional structure of graphene.
[0017] Preferably, the solid organic carbon source in step (2) is one or both of polymethyl methacrylate and polystyrene ester.
[0018] The beneficial effects brought about by the above-mentioned optimization include: the two raw materials have the advantages of good heat resistance, tough structure and low linear expansion coefficient.
[0019] Preferably, the spin coating speed in step (2) is 200 to 1000 rpm, and the spin coating time is 10 to 20 min.
[0020] Preferably, the spin coating adopts a step spin coating method, first spreading the organic carbon source at a low speed of 0 to 200 rpm, then adjusting the speed to 200 to 500 rpm, and setting the spin coating time to obtain a carbon coating with a thickness of 50 to 100 μm.
[0021] The beneficial effects brought by the above-mentioned optimization include: the progressive combination of high and low rotation speeds can make the spin coating structure more stable and uniform in structure, and easy to form.
[0022] Preferably, the ultrashort pulse laser in step (3) is one or a composite laser of nanosecond laser, picosecond laser and femtosecond laser.
[0023] Preferably, the wavelength of the ultrashort pulse laser beam in step (3) is 300 to 2000 nm, the spot diameter is 5 to 40 μm, the power is 5 to 50 W, and the scanning speed is 2 to 25 mm / s.
[0024] The beneficial effects brought about by the above-mentioned optimization include: the laser duration is short and the physical and chemical processes can be completed, and the preparation accuracy is high.
[0025] Preferably, the path and focal position in step (3) are determined by the designed three-dimensional porous structure of graphene.
[0026] Preferably, the thickness of the graphene layer in step (4) is determined by the thickness of the solder, and the porosity and cell shape of the graphene layer are determined by the brazing process parameters.
[0027] Another object of the present invention is to provide a method for preparing the above-mentioned graphene integrated intermediate layer for brazing of ceramic-based composite materials in the preparation of SiC f / SiC composite materials, C f / SiC composite materials, C f / C composite materials.
[0028] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention designs a graphene interlayer based on the brazing requirements and structural characteristics of ceramic-based composites, and uses laser direct writing to accurately prepare a graphene three-dimensional structure with controllable shape, porosity and thickness. The graphene three-dimensional porous structure combines the high temperature resistance and high stability of graphene itself with the energy absorption and buffering advantages of the three-dimensional porous skeleton, solving the inherent problems of poor temperature resistance of joints, difficult interface reaction control, and large residual stress in heterogeneous brazing of ceramic-based composites, and obtaining a high temperature resistant, high strength, and low stress joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0031] Figure 1 A flow chart of the preparation method and application of graphene integrated intermediate layer for brazing of ceramic-based composites;
[0032] Figure 2 Schematic diagram of the device for preparing graphene layers by laser direct writing;
[0033] Figure 3 This is a schematic diagram of the brazing assembly;
[0034] Among them, 1-ceramic matrix composite material, 2-integrated intermediate layer, 3-high temperature alloy, 4-brazing material 1#, 5-controllable graphene layer, 6-brazing material 2#;
[0035] Figure 4 This is a schematic diagram of the laser direct writing path of Example 1;
[0036] Figure 5 This is a schematic diagram of the laser direct writing path of Example 2;
[0037] Figure 6 The strength comparison between the graphene-containing intermediate layer joint and the direct brazing joint in Example 1 is shown;
[0038] Figure 7 The strength comparison between the graphene intermediate layer joint and the direct brazing joint in Example 2 is shown. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] 1. Brazing base material is SiC f / SiC ceramic matrix composites and Nb alloys;
[0042] 2. AuCuTi flake solder is used as the base material, with a size of 5mm×10mm×0.2mm, and is cleaned and dried;
[0043] 3. Based on this demand, the integrated intermediate layer design scheme is determined: the thickness of the graphene three-dimensional structure is 1mm, the cell shape is square-like, the porosity is 90%, and the size is 5mm×10mm.
[0044] 4. Apply an organic carbon source to the dried AuCuTi flake solder. Spin the organic carbon source at a low speed of 100 rpm, then adjust the speed to 400 rpm, and spin-coat for 20 minutes to evenly spin-coat the solid polymethyl methacrylate onto the solder substrate surface according to the solder size (5 mm × 10 mm), preparing a 1 mm thick uniform polymethyl methacrylate coating;
[0045] 5. Preparation of graphene three-dimensional structure by laser direct writing. Under the protection of Ar gas, the organic carbon coating was irradiated with a femtosecond laser. The optimized process parameters were a spot diameter of 20 μm, a power of 3 W, a scanning speed of 2 mm / s, and a rectangular scanning layer by layer in the carbon coating, such as Figure 4 According to the above steps, the three-dimensional porous graphene layer is prepared by direct writing and obtained to form a composite integrated intermediate layer with the solder substrate;
[0046] 6. Clean the excess graphene layer and cover the graphene layer with AuCuTi solder sheets of the same size (5mm×10mm) to form an integrated three-dimensional structure of graphene composite solder, which is in contact with the parent material SiC f / SiC ceramic matrix composite material and Nb alloy were assembled to form brazing samples and vacuum brazed. The brazing process parameters were 1100℃ for 20min;
[0047] 7. Determine the shear strength and compare it with the brazing joint of AuCuTi solder without intermediate layer, such as Figure 6 When there is no graphene intermediate layer, the joint shear strength is 23 MPa; when a commercial graphene metal intermediate layer is used, the joint shear strength is 43 MPa; when the graphene integrated intermediate layer is prepared by this method, the shear strength is 76 MPa.
[0048] Example 2
[0049] 1. Brazing base material is C f / C ceramic matrix composite material and GH536 nickel-based high temperature alloy;
[0050] 2. AuNiPd flake solder is used as the base material, with a size of 7mm×7mm×0.2mm, and is cleaned and dried;
[0051] 3. Based on this demand, the integrated intermediate layer design scheme is determined: the thickness of the graphene three-dimensional structure is 0.8 mm, the cell shape is pentagonal, and the porosity is 95%.
[0052] 4. Coat polystyrene ester on the dried AuNiPd sheet. Spin the organic carbon source at a low speed of 150 rpm, then adjust the speed to 500 rpm, and spin the solid organic carbon source onto the surface of the AuNiPd solder for 15 minutes to prepare a 1.5 mm thick coating.
[0053] 5. Preparation of graphene three-dimensional structure by laser direct writing. Under the protection of Ar inert gas, the organic carbon coating is irradiated with picosecond laser. The spot diameter is 10μm, the power is 20W, and the scanning speed is 5mm / s. The three-dimensional porous graphene layer and the brazing material composite integrated intermediate layer can be obtained by rectangular scanning layer by layer in the carbon coating, such as Figure 5 As shown;
[0054] 6. Clean the excess graphene layer and cover the graphene layer with another piece of brazing material of the same size and composition to form an integrated three-dimensional structure of graphene composite brazing material, assemble it with the base material to be welded to form a ceramic matrix composite brazing sample, and perform vacuum brazing connection. The brazing process parameters are 1180℃ for 20min;
[0055] 7. Determine the shear strength of the brazed joint and compare it with the brazed joint without the intermediate layer. Figure 7 When there is no graphene intermediate layer, the joint shear strength is 32MPa; when a commercial graphene metal intermediate layer is used, the joint shear strength is 47MPa; when the graphene integrated intermediate layer is prepared by this method, the shear strength is 96MPa.
[0056] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0057] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials, characterized in that: The following steps are involved: (1) Selecting a brazing filler metal suitable for ceramic matrix composites as the base material; (2) coating the organic carbon source: spin-coating the solid organic carbon source uniformly onto the surface of the substrate material according to the size of the solder to prepare an organic carbon source coating of uniform thickness; (3) Laser direct writing to prepare three-dimensional graphene structure: Under the protection of inert gas, ultrashort pulse laser is used to directly write and ablate the surface of the organic carbon source coating according to the set path and focus depth, so that the three-dimensional porous graphene layer prepared by direct writing and the substrate material form a composite integrated intermediate layer; (4) Clean the excess graphene layer and cover the graphene layer with another piece of brazing material of the same size and composition to form an integrated three-dimensional structure of the graphene composite brazing material, which is then assembled with the base material to be welded to form a ceramic-based composite material brazing sample and connected by vacuum brazing.
2. The method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials according to claim 1, characterized in that: The method for preparing the base material in step (1) comprises: if the solder is a powder, pressing the solder into sheets to obtain a sheet solder having a thickness of ≤0.2 mm as the base material; If the solder is in sheet form, select a sheet solder with a thickness of ≤0.2 mm as the base material; The size of the sheet solder should be at least 0.1 mm larger than the size of the surface to be soldered.
3. The method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials according to claim 1, characterized in that: The solid organic carbon source in step (2) is one or both of polymethyl methacrylate and polystyrene ester.
4. The method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials according to claim 1, characterized in that: The spin coating speed in step (2) is 200 to 1000 rpm, and the spin coating time is 10 to 20 minutes.
5. The method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials according to claim 4, characterized in that: The spin coating adopts a step spin coating method, firstly spreading the organic carbon source at a low speed of 0 to 200 rpm, then adjusting the speed to 200 to 500 rpm, and setting the spin coating time to obtain a carbon coating with a thickness of 50 to 100 μm.
6. The method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials according to claim 1, characterized in that: The ultrashort pulse laser in step (3) is one or more composite lasers selected from the group consisting of nanosecond laser, picosecond laser and femtosecond laser.
7. The method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials according to claim 1, characterized in that: The ultrashort pulse laser beam in step (3) has a wavelength of 300 to 2000 nm, a spot diameter of 5 to 40 μm, a power of 5 to 50 W, and a scanning speed of 2 to 25 mm / s.
8. The method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials according to claim 1, characterized in that: The path and focal position in step (3) are determined by the designed three-dimensional porous structure of graphene.
9. The method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composite materials according to claim 1, characterized in that: The thickness of the graphene layer in step (4) is determined by the thickness of the solder, and the porosity and cell shape of the graphene layer are determined by the soldering process parameters.
10. A method for preparing a graphene integrated intermediate layer for brazing of ceramic-based composites according to any one of claims 1 to 9 in the preparation of SiC f / SiC composite materials, C f / SiC composite materials, C f / C composite materials.
Citation Information
Patent Citations
Auxiliary brazing method for grapheme composite middle layer of three-dimensional structure
CN104625283A
Polyether-ether-ketone laser-irradiation-based graphene preparing method
CN109292759A
Method for assisting brazing of dissimilar materials through three-dimensional negative expansion network composite intermediate layer material
CN113231706A
Method for directly writing graphene pattern on nonmetal surface by laser
CN106057644A
Method for enhancing reduction resistance of brazed joint through graphene sponge barrier layer
CN112756727A